2013
DOI: 10.1371/journal.pone.0062624
|View full text |Cite
|
Sign up to set email alerts
|

Extracting the Information Backbone in Online System

Abstract: Information overload is a serious problem in modern society and many solutions such as recommender system have been proposed to filter out irrelevant information. In the literature, researchers have been mainly dedicated to improving the recommendation performance (accuracy and diversity) of the algorithms while they have overlooked the influence of topology of the online user-object bipartite networks. In this paper, we find that some information provided by the bipartite networks is not only redundant but al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 22 publications
0
45
1
Order By: Relevance
“…The main task of recommender system is to predict future links of each target user based on historical rating records [31,32,[35][36][37], in which the whole data set is divided into a training set and a test set and only the links in training set is known before recommendation. However, in most of the previous studies, as far as we know, the test data set is sampled randomly without consider the temporal order of the links, leading to a logical disorder in the recommendation process, i.e., predicting the past links in test set on the basis of the future links in training set.…”
Section: Related Workmentioning
confidence: 99%
“…The main task of recommender system is to predict future links of each target user based on historical rating records [31,32,[35][36][37], in which the whole data set is divided into a training set and a test set and only the links in training set is known before recommendation. However, in most of the previous studies, as far as we know, the test data set is sampled randomly without consider the temporal order of the links, leading to a logical disorder in the recommendation process, i.e., predicting the past links in test set on the basis of the future links in training set.…”
Section: Related Workmentioning
confidence: 99%
“…Motivated by the observed significant difference between users' structural properties in the network, Zhang et al proposed to remove redundant links for each user to extract the so-called information backbone [19]. Guan et al observed that large degree users tend to select niche objects while small degree users tend to select popular objects.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, two more recent algorithms are compared. The first one is called Most Popular Removal algorithm (MPR) which recommend items based on the information backbone of the user-item network [19]. The popularity of a link ia is defined as…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, there is a problem of information overload. The large amount of data generated every day makes it difficult for items we want to be chosen as easily as previously [2]. Personalized recommendation is considered the most effective way to solve the problem of information overload [3,4] and thus far, recommendation systems have been used in many fields [5][6][7].…”
Section: Introductionmentioning
confidence: 99%